2021
DOI: 10.5863/1551-6776-26.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low-Dose Epinephrine Continuous Infusion in Neonatal Intensive Care Unit Patients

Abstract: OBJECTIVES Although epinephrine is used in the neonatal intensive care unit, few data exist on efficacy of doses <0.05 mcg/kg/min. This study evaluates the efficacy and safety of low-dose epinephrine continuous infusion at doses <0.05 mcg/kg/min in infants. METHODS Single-center, retrospective review of hypotensive infants from 2011–2018. Charts were reviewed for initial and maximum epinephrine doses, additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…In this line are the results of a recent retrospective cohort study in 115 term and preterm infants with hypotension. It was found that continuous infusion of EPI at low doses (<0.05 mcg/kg/min) resulted in a significant improvement in AP and urine output in 55% of the patients, without adverse effects [126].…”
Section: Epinephrinementioning
confidence: 98%
See 1 more Smart Citation
“…In this line are the results of a recent retrospective cohort study in 115 term and preterm infants with hypotension. It was found that continuous infusion of EPI at low doses (<0.05 mcg/kg/min) resulted in a significant improvement in AP and urine output in 55% of the patients, without adverse effects [126].…”
Section: Epinephrinementioning
confidence: 98%
“…Studies on EPI administration to hypotensive neonates are very limited, especially when considering preterm neonates [51,65,126]. An early retrospective study involving 31 VLBWI (GA 23-30 weeks), who did not respond to DOP infusion up to 15 mcg/kg/min, showed that EPI infusion at doses ranging from 0.05 and 2.6 mcg/kg/min significantly increased mean AP and HR, with a parallel increase in the base deficit [67].…”
Section: Epinephrinementioning
confidence: 99%